2020
DOI: 10.1039/d0tb00342e
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic lanthanum-doped hydroxyapatite/chitosan scaffolds with endogenous stem cell-recruiting and immunomodulatory properties for bone regeneration

Abstract: Magnetic lanthanum hydroxyapatite/chitosan scaffolds can better repair bone defects through stem cell recruitment and immunomodulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 46 publications
0
35
0
Order By: Relevance
“…Hydroxyapatite, one form of calcium phosphate coating, has been widely used as a biocompatible scaffold for bioengineered bone implants (Wang et al, 2020;Yu et al, 2020;Zhu et al, 2020). However, it seems to have some certain type of acidity, whereas most reports have indicated that an alkaline environment inhibits the production of osteoclasts and promotes the proliferation of osteoblasts, thus reducing bone resorption (Arnett and Dempster, 1986;Arnett, 2008;Galow et al, 2017).…”
Section: Characterization and In Vitro Mineralization Of B-bgsmentioning
confidence: 99%
“…Hydroxyapatite, one form of calcium phosphate coating, has been widely used as a biocompatible scaffold for bioengineered bone implants (Wang et al, 2020;Yu et al, 2020;Zhu et al, 2020). However, it seems to have some certain type of acidity, whereas most reports have indicated that an alkaline environment inhibits the production of osteoclasts and promotes the proliferation of osteoblasts, thus reducing bone resorption (Arnett and Dempster, 1986;Arnett, 2008;Galow et al, 2017).…”
Section: Characterization and In Vitro Mineralization Of B-bgsmentioning
confidence: 99%
“…[ 63 ] In addition, the incorporation of functional molecules or agents in scaffolds to modulate recruited macrophages has also drawn the interest of researchers. Biomolecules such as 25‐hydroxyvitamin D3, [ 64 ] SEW2871, [ 65 ] aspirin‐triggered resolvin D1, [ 66 ] polymerizable fucoidan and carrageenans, [ 67 ] lanthanum, [ 68 ] and sericin [ 69 ] capable of promoting M2 macrophage polarization or anti‐inflammatory processes were applied and investigated. Surface coatings for immune evasion have been widely investigated on synthetic material‐derived grafts as stealth coatings.…”
Section: Immunocompatibility Of Engineered Tissue or Organ‐based Implantsmentioning
confidence: 99%
“…In fact, the cytocompatibility and biodegradability of chitosan even when mixed with gold [72], silver [73] and iron oxide nanoparticles proposed this natural polymer as a suitable candidate for tissue engineering. CS is largely used in a mixture with several materials [74], including hydroxyapatite [75]. For example, it is possible to promote an in situ precipitation procedure to obtain very uniform and homogenous chitosan/hydroxyapatite and chitosan/hydroxyapatite/MNPs scaffolds using genipin with the double role of biocompatible material for improving the osteointegration and as a crosslinker agent [76].…”
Section: Mnps Enriched Scaffolds Without the Application Of An Externmentioning
confidence: 99%
“…In vivo tests, performed on bone defects induced in rabbit radius, showed that the bone regeneration process was accelerated with an increase in bone mineral density, percentage of bone volume/tissue volume ratio and new bone area formation in the presence of MNPs and an external magnetic field. The in vivo bioactivity of bone scaffold based on CS/n-HA was further increased using lanthanum doping [75], even though this biological mechanism is not still completely clear. In particular, SrFe12O9 M-type hexagonal ferrite was used to give magneto-responsive behavior to lanthanum doped CS/n-HA (MNPs-La-CS/n-HA) scaffolds.…”
Section: Mnps Enriched Scaffolds With the Application Of External Magmentioning
confidence: 99%
See 1 more Smart Citation